IDENTIFIKASI SIFAT FISIKOKIMIA DAN ORGANOLEPTIK SUSU NABATI YANG DIFORMULASIKAN DENGAN LINEAR PROGRAMMING - Sentana, Aileen; Trisnawati, Chatarina Yayuk; Jati, Ignasius Radix Astadi Praptono (Jurnal Teknologi Pangan dan Gizi, 2017)
The milk consumption level in Indonesia is relatively low due to some people who has lactose and casein intolerance, the unpleasant milk aroma and its high price. Vegetable milk can be used to substitute cow milk using nuts as the main ingredients. Canarium nut and almond nut as the fat sources and red bean and also cowpea as the protein sources can be combined together to produce mixed nut milk. Mixed nut milk will be formulated using linear programming. The formulations were formulated based on the protein and fat content optimization and minimizing production cost. Each mixed nut formulations that were going to be tested in the study will be repeated three times. Different mixed nut milk formulation produced different end product characteristics as well. The characteristics of the various mixed nut milk formulations were compared in order to determine the most desirable mixed nut milk formulation. The test showed that there was significant different totals solid content, protein content, fat content, colour, viscosity and overall acceptance such as colour, viscosity and flavour of mixed nut milk due to different formulation. The highest protein content that can be reached from those three formulations was 2.86%, meanwhile the highest fat content was 6.17%. The research result also showed that the formulation based on the highest fat content had the most similar viscosity compared to cow milk (0.0020 Pas) which is 0.0038 Pas. This formulation also had the highest acceptance level especially in flavours with 3.60 point from 1-5 scale. This mixed nut milk is expected to be able to increase the milk consumption level in Indonesia and can be used as an alternative choice to substitute cow milk.